2018
DOI: 10.1093/jee/toy041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Storage and Granary Weevil Infestation on Gel Electrophoresis and Protein Solubility Properties of Hard and Soft Wheat Flours

Abstract: The objective of this study was to investigate the effects of storage and granary weevil, Sitophilus granarius (L.; Coleoptera: Curculionidae), infestation on pH, protein solubility (PS) and gel electrophoresis properties of meal and roller-milled flours of hard (Ceyhan-99 cv.) and soft (Eser cv.) wheat cultivars, respectively, after 6 mo of storage. Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) technique was applied for studying the electrophoretic properties. Hard and soft wheats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Previous reports also indicated that physiological properties in wheat can vary with the degree of hardness during accelerated ageing. Additionally, the post-harvest storage-tolerance of soft and hard wheat was different under the same storage conditions (Keskin et al, 2018;Zhang et al, 2017). Our current results showed that the Gr of soft wheat seeds of the 'Yangmai 15' cultivar was higher than that of hard wheat seeds of the 'Aikang 58' cultivar under the same storage conditions (Lv et al, 2016), confirming the superior post-harvest storage-tolerance of soft wheat.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous reports also indicated that physiological properties in wheat can vary with the degree of hardness during accelerated ageing. Additionally, the post-harvest storage-tolerance of soft and hard wheat was different under the same storage conditions (Keskin et al, 2018;Zhang et al, 2017). Our current results showed that the Gr of soft wheat seeds of the 'Yangmai 15' cultivar was higher than that of hard wheat seeds of the 'Aikang 58' cultivar under the same storage conditions (Lv et al, 2016), confirming the superior post-harvest storage-tolerance of soft wheat.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 56%
“…In wheat, kernel texture and biochemical composition vary with the degree of hardness (Lesage et al, 2011;Pasha et al, 2010). Previous researches showed that seed ageing causes the physiological and biochemical variation including differences in hardness during storage, and these changed characteristics have been extensively studied, specifically changes in antioxidants, free radicals, storage proteins, and respiration (Galleschi et al, 2002;Calucci et al, 2004;Keskin et al, 2018; PeerJ reviewing PDF | (2018:06:28953:1:0:NEW 1 Sep 2018)…”
Section: Introductionmentioning
confidence: 99%
“…[8,60,63,64]. Though some have found higher infestation and greater abundance of S. granarius on soft wheat compared with durum wheat cultivars [65,66], this could be because the main digestive enzyme for S. granarius is amylase [67]. Nawrot et al [60] found that seven times more amylase was present in S. granarius fed on soft wheat cultivars than on durum wheat cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports also indicated that physiological properties in wheat can vary with the degree of hardness during accelerated ageing. Additionally, the post-harvest storage-tolerance of soft and hard wheat was different under the same storage conditions ( Keskin, Yalçın & Özkaya, 2018 ; Zhang et al, 2017 ). Our current results showed that the Gr of soft wheat seeds of the ‘Yangmai 15’ cultivar was higher than that of hard wheat seeds of the ‘Aikang 58’ cultivar under the same storage conditions ( Lv et al, 2016 ), confirming the superior post-harvest storage-tolerance of soft wheat.…”
Section: Discussionmentioning
confidence: 99%
“…In wheat, kernel texture and biochemical composition vary with the degree of hardness ( Lesage et al, 2011 ; Pasha, Anjum & Morris, 2010 ). Previous researches showed that seed ageing causes the physiological and biochemical variation including differences in hardness during storage, and these changed characteristics have been extensively studied, specifically changes in antioxidants, free radicals, storage proteins, and respiration ( Galleschi et al, 2002 ; Calucci et al, 2004 ; Keskin, Yalçın & Özkaya, 2018 ; McDonald, 1999 ; Zhang et al, 2017 ). Previous studies also indicate that the seed ageing effects the proteome of dry seeds ( Rajjou et al, 2008 ; Xin et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%